Potencial reprodutivo de Chrysoperla externa (Neuroptera: Chrysopidae): Efeito da proporção sexual e período de acasalamento - Pessoa, Luis G.A.; De Freitas, Sérgio [UNESP]; Loureiro, Elisângela de S. (Revista Brasileira de Ciencias Agrarias, 2013)
In this study the effects of the time of male permanence with females and different sex ratios on the reproductive capacity of Chrysoperla externa F 3 adults was evaluated. The insects were kept at 25 ± 2 °C, 70 ± 10% RH, under a 12 h photoperiod. The first experiment consisted of mating females with males that were subsequently removed after 5, 10, 15, 20, 25, 30, 35 and 40 days; the control group consisted of males remaining with the females during the entire experimental period. The second experiment consisted of mating: one male with one female (1:1); one male with two females (1:2); one male with three females (1:3); one male with four females (1:4); and one male with five females (1:5), and then evaluating their pre-ovipositioning periods, daily and total ovipositioning, egg viability percentages, and efficiency indices (which considered total ovipositioning, mean egg viability, and the ovipositioning period). It was found that alternating the sexual proportions from one male with one female to one male with three females did not alter the reproductive performance of these insects, and that there was no need to replace the males after five days as they were able to provide sufficient numbers of spermatozoa during this period to maintain consistent reproductive rates.
Reproductive capacity of Chrysoperla externa (Neuroptera: Chrsyopidae): Effect of sexual proportion and mating time
Keywords: Green lacewing; Mass rearing; Predator; Reproductive capacity